2007
DOI: 10.1093/jn/137.4.1097
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Food-Processing and Preparation Practices to Enhance the Bioavailability of Micronutrients in Plant-Based Diets1

Abstract: Dietary quality is an important limiting factor to adequate nutrition in many resource-poor settings. One aspect of dietary quality with respect to adequacy of micronutrient intakes is bioavailability. Several traditional household food-processing and preparation methods can be used to enhance the bioavailability of micronutrients in plant-based diets. These include thermal processing, mechanical processing, soaking, fermentation, and germination/malting. These strategies aim to increase the physicochemical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
283
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 424 publications
(299 citation statements)
references
References 27 publications
5
283
1
10
Order By: Relevance
“…Unfortunately, it is also associated with proliferation of microorganisms such as yeast and molds that may cause food safety concerns (Omemu, 2011), reduction in provitamin A and antioxidant carotenoids (Ortiz, Nkhata, Buechler, Rocheford, & Ferruzzi, 2017), as well as loss of vitamins and minerals (Hotz & Gibson, 2007). …”
Section: Fermentationmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, it is also associated with proliferation of microorganisms such as yeast and molds that may cause food safety concerns (Omemu, 2011), reduction in provitamin A and antioxidant carotenoids (Ortiz, Nkhata, Buechler, Rocheford, & Ferruzzi, 2017), as well as loss of vitamins and minerals (Hotz & Gibson, 2007). …”
Section: Fermentationmentioning
confidence: 99%
“…Tang and Zhao (1998) concluded that the PAL activity is enhanced during the process of germination. Another possible explanation is that there could be hydrolysis of bound phenolic compounds as well as de novo biosynthesis of phenols in the embryonic axis of the sprouts (Hotz & Gibson, 2007; Onyango et al., 2013; Zilic et al., 2015). The increased content of phytochemicals results into increased antioxidant activity of germinated cereals and legumes.…”
Section: Effect Of Germination or Malting On Nutrients And Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Batch-2 substrates with higher sugars level tend to exert osmotic stress on cells than Batch-1 substrates [24,27,29]. Furthermore, the additional presence of lignin-derived phenolic compounds liberated during mashing (predominantly from husks materials) may further exacerbate environmental stress on P. stipitis cells [16,27,29,30]. KSV8 substrate consistently showed faster and higher fermentation rates in terms of CO 2 production by both S. cerevisiae and P. stipitis (Fig.…”
Section: Fermentationmentioning
confidence: 97%
“…Interestingly, in spite of observed residual FAN, P. stipitis was unable to appreciably utilise available xylose. This may be reflective of the cells impaired fermentative capacity as ethanol concentration in the media increases [28][29][30].…”
Section: Fermentationmentioning
confidence: 99%